The thermodesorption mechanism of ammonia from Ru(0001) - Tautermann, C; Wellenzohn, B; Clary, D (2006)
Thermodesorption rates for the desorption of ammonia from Ru(0 0 0 1) are calculated by Transition State Theory including small curvature tunneling corrections. The potential energy surface is derived on a model cluster employing hybrid density functional theory (B3LYP). Two desorption pathways can be identified, just distinguished by the orientation of the leaving ammonia entity. It is found that the rate dominating mechanism comprises an umbrella-like flipping movement of the hydrogen atoms during the desorption. Nevertheless tunneling does not play any significant role in the reaction as the hydrogen movements are shown to occur at the low energy regions of the barrier. © 2006 Elsevier B.V. All rights reserved.